Modeling aortic stenosis progression: impact on follow-up, treatment and survival. (3rd October 2022) - Teixeira, R; Ribeiro, D; Sousa Nunes, F; Leite, M; Neves, A; Santos, D; Silva, M; Silva, G; Diaz, S; Saraiva, F; Sampaio, F; Fontes-Carvalho, R
Abstract: Background: Aortic stenosis (AS) is one of the main valvular heart diseases in developed countries. Degenerative fibrocalcific aortic stenosis is a progressive disease of the valve and ultimately of the myocardium, which can be fatal when symptomatic. There is no medical treatment that can halt or delay its progression. AS does not evolve linearly over time, and not every patient has the same progression rate. Aims: The aim of this study is to 1) compare different mathematical models of aortic stenosis progression, 2) cluster patients into rapid and slow progressors and explore possible predictors, 4) evaluate the impact of different progression rates on cardiac structure and function, and 5) evaluate survival and optimal timing for follow-up and treatment. Methods: We retrospectively studied consecutive patients with aortic peak velocities from 2012 to 2020. Follow-up echocardiograms, seriated biomarker assessment, and clinical records were consulted, providing a multiparametric data frame for longitudinal and dynamic modeling of aortic stenosis progression and its consequences. Results: This study included 9583 studies from 752 patients with a median total follow-up of 4.26 years (interquartile range: 1.28 to 7.24 years). A logistic model was selected with the best accuracy to predict the rate of AS progression. Patients were categorized into slow and rapid progressors in a ratio of 5:1. Multiparametric analysis showed no association between these profiles and clinical variables. However, anti-hypertensive drugs before and after adjustment for blood pressure control (Calcium Channel Blockers, p=0.013, OR 0.50) were associated with slower progression. Meanwhile, elevated inflammatory markers (erythrocyte sedimentation rate, p=0.01) were associated with faster AS progression. Despite no survival difference between these groups, higher rates of valvular intervention were registered in rapid progressors (p<0.001). Moreover, faster progressors were associated with earlier cardiac damage (as demonstrated by early onset of moderate mitral and tricuspid valve regurgitation, left auricle dilation, and left ventricle hypertrophy, p<0.05). Conclusions: These results can potentially modify follow-up times and deliver more personalized and individualized health care to different AS patients, thereby optimizing resources. Funding Acknowledgement: Type of funding sources: None.